Phenotypic variation in Heremites vittatus (Olivier, 1804) (Sauria: Scincidae) from Iran and Turkey - Rastegar-Pouyani, Nasrullah; Kumlutaş, Yusuf; Avci, Aziz; Candan, Kamil; Ilgaz, Cetin; Fattahi, Razieh; Yousefkhani, Seyyed Saeed Hosseinian (Zootaxa, 2021)
According to a large morphological dataset of specimens from Turkey to Iran and based on several morphological analyses, the Iranian populations of the skink Heremites vittatus are separated from other populations of this taxon in Turkey. The values of most of morphological characters were higher in the Turkish populations. Morphological variation among populations of H. vittatus (Olivier, 1804) from Turkey and the western slopes of the Zagros Mountains in Kermanshah province in Iran may be the result of different dispersal and vicariance events. Comparison the current study dataset with specimens from Egypt can definite the taxonomic status of Iranian and Turkish populations.